Report on proposed new interior design of Iskandar information Centre for Iskandar Regional Developemen Authority at ‘Bay Leaf’ Danga Bay Jalan Skudai, 80200 Johor Bahru / Muhammad Rahmat Mohammad Radzi - Mohammad Radzi, Muhammad Rahmat (Faculty of Architecture, Planning and Surveying, 2010)
As accomplishing the final stage of learning process, a comprehensive design proposal needs to be prepare by each of students. The project that had been chosen for this final project is to propose a New Interior Design of Iskandar Information Centre for Iskandar Regional Development Authority (IRDA) at Bay Leaf Danga Bay Jalan Skudai, 80200 Johor Bahru. This proposed Information Centre is to attract investor, both local and overseas to invest in Iskandar and to design a very different Information Centre compare others in Malaysia. Concept and image that had been chosen not only has to be appropriate and suitable, but it must have a strong impact towards the design purposes, where it will give a strong character to the site. Connected to that, the chosen design style for this information centre is based on high-tech design, which is corresponding with the client’s requirements and needs. As fulfilling the design according to the clients’ desires and needs, some research and data analysis has been done. Some of the information of the study is through interview, observation, internet, book reference, and through the result from the case studies either locally or internationally.